Improving Ambulance Mission Progress Tracking in Sweden - Ahammer, Marina; Persson Palmqvist, Kasper (My University, 2024)
This master’s thesis project aims to investigate present-day prehospital care, especially focusing on ambulance care in Sweden. This project targets the system that tracks progress during an ambulance mission. The system consists of six steps which have to be manually confirmed by the ambulance nurses at the press of a button. The interaction between the ambulance nurses and the system registers the time duration between the different steps of the mission. The goal was to map out unknowns in the system and propose a feasible solution to increase the tracking efficiency and minimise false time registration. During the project, three steps have been automated while two which are not yet tracked, have been added. Further, the project does not only touch technology but also the ambulance nurses’ cognitive workload. The project is executed in collaboration with PICTA – Prehospital Innovation Arena located at Lindholmen’s Science Park in Gothenburg.
Keywords: Prehospital ambulance care; Human machine interaction; User research; Co-design; System thinking